A relationship of porosity and mechanical properties of spark plasma sintered scandia stabilized zirconia thermal barrier coating - Iqbal, AKM Asif; Lim, Mei Jing (Elsevier B.V., 2023)
Porous ceramic materials are popularly accepted as thermal barrier coatings (TBCs) in insulating gas turbine parts working at high temperatures. In this research, three different types of Scandia stabilized zirconia (ScSZ) systems, a nanometric 10 mol% ScSZ (10-ScSZ), a micrometric 8 mol% ScSZ (8-ScSZ) and a combination of these two powders (10-8-ScSZ) have been developed by Spark Plasma Sintering (SPS) process. Varying SPS parameters, for instance, temperature, pressure and dwell time were applied to develop the different volumes of porosity in the materials. Subsequently, the microstructure of the materials has been studied and mechanical properties have been evaluated. All three materials demonstrate a reduced porosity level at high sintering temperature and pressure. However, the nanometric 10-ScSZ material shows a higher reduction of porosity from 51.8% to 11.1% at 30 MPa pressure and 40.2%–8.5% at 60 MPa pressure within the temperature range of 1000–1200 °C. Besides, the 10-8-ScSZ composite exhibits substantially increased porosity in comparison to its constituent parts. The results also show that the nanometric 10-ScSZ material exhibits a greater mechanical strength including Vickers microhardness of 81 HV, flexural strength of 361 MPa and elastic modulus of 187 GPa at 5% porosity level, as compared to the other two materials. Additionally, it is observed that all the mechanical properties for all three materials consistently decrease with the increase in porosity levels. While compared with the traditional atmospheric plasma spray (APS) processed ceramic coating, the porous ScSZ coating materials exhibit a larger elastic modulus. Therefore, the porous ScSZ developed by the SPS process could be a prospective alternative thermal barrier coating (TBC).